ANALYSIS OF MACROECONOMIC EFFECT ON JAKARTA ISLAMIC INDEX - Gunariah, Frilla; Nurdiansyah, Irdan (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the impact of inflation, gold prices, and exchange rates on the Jakarta Islamic Index (JII) stock price index during 2013-2023. The background of this research is based on the importance of understanding macroeconomic factors that affect the movement of stock indices, especially the Jakarta Islamic Index (JII). As one of Indonesia's leading Sharia stock indices, JII is a reference for investors in determining investment decisions per Sharia principles. Using a descriptive-verificative method with a quantitative approach, the study utilized secondary data from 30 companies listed in the JII and analyzed it with Eviews9. The results indicate that, simultaneously, inflation, gold prices, and exchange rates significantly influence the JII stock price index by 93.35%, while the remaining 6.65% is affected by other factors outside the model. Partially, inflation and gold prices have a significant effect, whereas exchange rates do not significantly impact the JII stock price index. These findings confirm that macroeconomic variables play a crucial role in the movement of the Islamic stock index.